Policing, young people, diversion and accountability in Ireland - Kilkelly, Ursula (Crime, law and social change, 2011)
The Irish police practice of diverting young offenders was placed within a statutory framework in 2001. The police discretion in the management of young offenders that had been a feature of the administrative process was retained at the heart of the new statutory programme although attempts were made to streamline the process. This article critiques the law, policy and practice underpinning the exercise of that discretion against the relevant international human rights standards on transparency, accountability and professionalism in juvenile justice. It reveals how the management of the programme in practice falls short of these standards and, in particular, the due process rights of the children who come within its reach. It argues that the root of the problem lies primarily in the lack of published criteria to guide the discretionary decision-making at several stages of the programme, and the lack of a credible complaint or review mechanism for the children affected. It recommends the publication of reasons for decisions taken in the exercise of Garda discretion in individual cases, together with provision for review or appeal of such decisions as well as regular independent monitoring of the operation of the programme as a whole.